Temporal variations of fine and coarse particulate matter sources in Jeddah, Saudi Arabia. (1st February 2018) - Lim, Chris C.; Thurston, George D.; Shamy, Magdy; Alghamdi, Mansour; Khoder, Mamdouh; Mohorjy, Abdullah M.; Alkhalaf, Abdulrahman K.; Brocato, Jason; Chen, Lung Chi; Costa, Max
ABSTRACT: This study provides the first comprehensive analysis of the seasonal variations and weekday/weekend differences in fine (aerodynamic diameter <2.5 μm; PM2.5 ) and coarse (aerodynamic diameter 2.5–10 μm; PM2.5–10 ) particulate matter mass concentrations, elemental constituents, and potential source origins in Jeddah, Saudi Arabia. Air quality samples were collected over 1 yr, from June 2011 to May 2012 at a frequency of three times per week, and analyzed. The average mass concentrations of PM2.5 (21.9 μg/m 3 ) and PM10 (107.8 μg/m 3 ) during the sampling period exceeded the recommended annual average levels by the World Health Organization (WHO) for PM2.5 (10 μg/m 3 ) and PM10 (20 μg/m 3 ), respectively. Similar to other Middle Eastern locales, PM2.5–10 is the prevailing mass component of atmospheric particulate matter at Jeddah, accounting for approximately 80% of the PM10 mass. Considerations of enrichment factors, absolute principal component analysis (APCA), concentration roses, and backward trajectories identified the following source categories for both PM2.5 and PM2.5–10 : (1) soil/road dust, (2) incineration, and (3) traffic; and for PM2.5 only, (4) residual oil burning. Soil/road dust accounted for a major portion of both the PM2.5 (27%) and PM2.5–10 (77%) mass, and the largest source contributor for PM2.5 was from residual oil burning (63%). Temporal variations of PM2.5–10 and PM2.5 were observed, with the elevated concentration levels observed for mass during the spring (due to increased dust storm frequency) and on weekdays (due to increased traffic). The predominant role of windblown soil and road dust in both the PM2.5 and PM2.5–10 masses in this city may have implications regarding the toxicity of these particles versus those in the Western world where most PM health assessments have been made in the past. These results support the need for region-specific epidemiological investigations to be conducted and considered in future PM standard setting. Implications : Temporal variations of fine and coarse PM mass, elemental constituents, and sources were examined in Jeddah, Saudi Arabia, for the first time. The main source of PM2.5–10 is natural windblown soil and road dust, whereas the predominant source of PM2.5 is residual oil burning, generated from the port and oil refinery located west of the air sampler, suggesting that targeted emission controls could significantly improve the air quality in the city. The compositional differences point to a need for health effect studies to be conducted in this region, so as to directly assess the applicability of the existing guidelines to the Middle East air pollution.